2013
DOI: 10.5194/bgd-10-15519-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Springtime phytoplankton dynamics in the Arctic Krossfjorden and Kongsfjorden (Spitsbergen) as a function of glacier proximity

Abstract: The hydrographic properties of the Kongsfjorden – Krossfjorden system (79° N, Spitsbergen) are affected by Atlantic water incursions as well as glacier meltwater runoff. This results in strong physical gradients (temperature, salinity and irradiance) within the fjords. Here, we tested the hypothesis that glaciers affect phytoplankton dynamics as early as the productive spring bloom period. During two campaigns in 2007 (late spring) and 2008 (early spring) we studied hydrographic characteristics and phytoplankt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Many parameters, including particulate material, salinity, chlorophyll, dissolved nutrients and temperature, are known to vary along the length of Kongsfjorden and might impact bacterial community structure . In the present study, inner fjord (IF) station was located near to the Kongsbreen glacier thus experience heavy glacier meltwater influx loaded with dissolved nutrients (N and P), and organic matter of terrigenous origin during summer .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Many parameters, including particulate material, salinity, chlorophyll, dissolved nutrients and temperature, are known to vary along the length of Kongsfjorden and might impact bacterial community structure . In the present study, inner fjord (IF) station was located near to the Kongsbreen glacier thus experience heavy glacier meltwater influx loaded with dissolved nutrients (N and P), and organic matter of terrigenous origin during summer .…”
Section: Discussionmentioning
confidence: 95%
“…However, some studies reported their presence in both particle‐associated and free‐living fractions , as observed in our study with some differences in their relative abundance between both fractions. Firimicutes have been reported as a dominant phylum in Arctic permafrost , high Arctic snow , and meltwater streams . Therefore, higher incidence of Firmicutes in the IF_FL fraction could indicate enhanced terrestrial and glacier inputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During June and September, the glacial melt water input could be higher as evident by the lower salinity values in the upper water column. High sediment concentrations derived from the input of melted glacial water can limit the light availability for phytoplankton growth near the glaciers 12 . The euphotic zone can be restricted to the upper 0.3 m close to the glaciers, 22 leading to highly unfavorable conditions for phytoplankton growth 23 …”
Section: Discussionmentioning
confidence: 99%
“…In the recent studies of Piquet et al11, 12 on the pelagic microbial communities of Kongsfjorden, the diversity of non-culturable communities of bacteria, phytoplankton, and protists was monitored. However, very few attempts have been made to understand the diversity of retrievable heterotrophic bacteria of this ecosystem 13, 14…”
Section: Introductionmentioning
confidence: 99%